Mind-Body Exercises: What Do We Know So Far? An Update (International Journal of Physiotherapy, 2025)
Background: Mind-body exercises encompass yoga, Tai Chi, Body-Oriented Psychotherapy, mindfulness-based therapies and meditation, Feldenkrais, the Alexander Method, Breath Therapy, and massage, as well as mental training. These exercises focus on enhancing athletic performance and sports performance, improving overall health, and developing body awareness. This extensive study aims to understand the philosophical tenets, methodologies, motivations, extent, and efficacy of the Mind-Body Exercises and their role in artificial intelligence.Methods: Global studies were included to analyse the impact of mind-body exercises.Results: Research has demonstrated that mind-body exercises can significantly improve a spectrum of health outcomes, intricately influencing neural structures to promote physical and mental well-being. The exercises can also help with cognitive, balance, and pulmonary functions, mitigate pain perception, anxiety, and depression, and elevate subjective wellbeing. Even cancer survivors can benefit from practicing mind-body exercises, which can improve factors such as physical fitness, fatigue, sleep quality, depression, anxiety, and body mass index. The theoretical framework of mind-body emphasizes the connection between the mind and body. Disturbances in these connections evoke distress, necessitating practices that elevate body awareness, emphasising the pivotal role of patient-therapist interactions in fostering integration and profound unity between self and body.Conclusion: Mind-body exercises have the potential to enhance physical and cognitive health, promote body awareness, and improve overall well-being. The integration of artificial intelligence in yoga shows promise for enhancing practice and preventing injuries. Future research should investigate age- and gender-specific effects and conduct nuanced comparisons between meditation-only, conventional exercise-only, and mind-body exercises to examine their impact on the brain. Rigorous randomised controlled trials are strongly recommended for a precise understanding across diverse populations, necessitating judicious interpretation of findings, robust study designs, and comprehensive assessments to unveil the multifaceted benefits of mind-body exercises.